Effects of inefficiency on marginal costs, degree of economies of scale and technical change: A theoretical relationship; Efectos de la ineficiencia sobre los costes marginales, el grado de economías de escala y el cambio técnico: Una relación teórica - Juan José Díaz-Hernández; Eduardo Martínez-Budría; Rosa M. González Marrero (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2020)
In this paper, a theoretical relationship is obtained to measure the effect that inefficiency has on marginal costs, degree of economies of scale and technical change. It is shown that when the relationship between inefficiency and output level is ignored, the estimation of marginal costs and the degree of economies of scale are incorrect. The measurement of technical change is also wrongly calculated if one does not consider the variation of inefficiency over time. This could lead to incorrect pricing decisions that would transfer inefficiency to the consumer via prices and non-optimal investments in productive capacity. In addition, the effect of technical change on costs could be erroneously estimated. The empirical application of this theoretical model to Spanish port authorities during the period 2008-2016 shows that marginal costs of port services were overestimated, the degree of economies of scale was underestimated and the time variations of the inefficiency were interpreted erroneously as technical change when the relationship between inefficiency and output and time is not considered.
Keywords: C13; C51; D24; L11; L25; 330; cost efficiency; marginal cost; degree of economies of scale; technical change; ports